2018
DOI: 10.1016/j.jss.2018.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Software startup engineering: A systematic mapping study

Abstract: Context] Software startups have long been a significant driver in economic growth and innovation. The on-going failure of the major number of startups calls for a better understanding of state-of-the-practice of startup activities.[Objective] With a focus on engineering perspective, this study aims at identifying the change in focus of research area and thematic concepts operating startup research. [Method] A systematic mapping study on 74 primary papers (in which 27 papers are newly selected) from 1994 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 52 publications
2
78
0
2
Order By: Relevance
“…Innovation and startup driven publications make up a smaller chunk of interest, and this might be particularly critical for SEE following industry trends [19] as the validity to industry of the courses should be continuously addressed. Similar mapping studies [69] showed the present startup diffusion and challenges in industry.…”
Section: Discussionsupporting
confidence: 75%
“…Innovation and startup driven publications make up a smaller chunk of interest, and this might be particularly critical for SEE following industry trends [19] as the validity to industry of the courses should be continuously addressed. Similar mapping studies [69] showed the present startup diffusion and challenges in industry.…”
Section: Discussionsupporting
confidence: 75%
“…Customer feedback highlights new functionality and improvements. As long-term planning is infeasible in the chaotic environment of startups, flexibility and reactiveness are necessary [18].…”
Section: Product Development In Startupsmentioning
confidence: 99%
“…Software start-ups are small companies created to build and market a software-intensive product [1]. Start-ups are characterized by rapid evolution, small teams, uncertainty about customer needs and market conditions, and a high failure rate [2], [3]. However, leveraging cutting-edge technologies, risk, and speed, start-ups can launch software products fast [4], [5].…”
Section: Introductionmentioning
confidence: 99%